Cevaplar

2013-02-04T16:39:37+02:00

P(-1)=-2

P(1)=6

 

p(x)=(x-1).(x+1)+ax+b

P(1)=a+b=6

P(-1)=-a+b=-2

             

            iki denklemi topla

                2b=4

                   b=2

                    a=4

 

kalan 4x+2 dir

0
  • Eodev Kullanıcısı
2013-02-04T16:44:07+02:00

P(-1)=-2

P(1)=6

 

p(x)=(x-1).(x+1)+ax+b

P(1)=a+b=6

P(-1)=-a+b=-2

             

            iki denklemi topla

                2b=4

                   b=2

                    a=4

 

kalan 4x+2 dir.

0